Aspects of emotional labor of public health nurses engaged in interpersonal support - Junko Honda; Akiko Sasaki; Shio Tsuda; Machiko Matsuyama; Kumiko Morita (Wiley, 2023)
Abstract Aim Clarifying the emotional labor of public health nurses while providing interpersonal support. Design Qualitative descriptive study conducted using content analysis to clarify the aspect of emotional labor of PHNs regarding interpersonal support. Methods Individual semi‐structured interviews were conducted with 28 public health nurses employed by seven city governments in Japan. The data items obtained were categorized using deductive content analysis. Results When attempting interpersonal support, PHNs showed the following aspects of emotional labor: (1) negative emotions towards residents and resident‐focused emotions; (2) emotional rules based on duty performance, emotional rules based on fairness, emotional rules based on intimacy; (3) adaptive emotional regulation, maladaptive emotional regulations and (4) emotional expressions based on friendliness, emotional expressions based on calmness. Conclusion PHNs used adaptive emotional regulation in some cases and sometimes resorted to maladaptive forms. A system of support should be established to ensure the smooth and effective provision of interpersonal support.